WOMEN’S PARTICIPATION IN THE PROCESS OF CODIFICATION OF THE CRIMINAL CODE IN ACEH - Zuriah Zuriah; Muchlis Bahar; Elfia (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyse the form of women’s participation in the process of formulating the Qanun Jinayah in Aceh and its implications for strengthening the perspective of gender justice in Islamic sharia regulations. The Qanun Jinayah is a regional legal product that emerged from Aceh’s special authority in implementing Islamic law and forms part of the process of transforming fiqh norms into a regional positive legal system. However, women’s involvement in the process of formulating these regulations remains a crucial issue because the substance of the qanun is directly related to issues affecting women’s lives. This research employs a normative juridical research method with a conceptual and historical approach. Data were obtained through a literature review of various primary, secondary, and tertiary legal sources. Data analysis was conducted qualitatively by interpreting and connecting various relevant literature. The findings indicate that women’s participation in the process of codifying the Qanun Jinayah remains relatively limited, both in formal and informal spheres. Women’s involvement is evident through several channels, such as the presence of female legislators in the Aceh People’s Representative Council, the contribution of female academics in the study and preparation of academic papers, the role of civil society organisations, and social participation within community groups. However, women’s representation in the decision-making process remains suboptimal, resulting in women’s perspectives and ex ’s experiences not being fully incorporated into the substance of regulations. Therefore, this study recommends strengthening mechanisms for women’s participation in the Qanun legislative process, increasing women’s representation in legislative institutions, and actively involving women in the development of academic texts and public discourse to ensure that the resulting Sharia regulations are more inclusive, responsive, and gender-equitable.